Faktor-Faktor yang Memengaruhi Audit Delay pada Perusahaan Industri Energi dan Industri Baja yang Terdaftar di Bursa Efek Indonesia (2020-2024) - Melati, Putri; Doni, Amsah Hendri (ARZUSIN, 2026)
Audit delay has become a concern in accounting and auditing studies because it is related to the timeliness of financial statement submission and the quality of information for stakeholders. However, research specifically examining the influence of company age, company size, auditor opinion, and the size of Public Accounting Firms (KAP) on audit delay in energy industry and steel industry companies remains limited. This study aims to analyze the influence of company age, company size, auditor opinion, and KAP size on audit delay in energy industry and steel industry companies listed on the Indonesia Stock Exchange for the 2020–2024 period. This study used a quantitative approach with a causality design. The research sample consisted of 19 companies selected through purposive sampling, with a total of 95 observational data. Data were collected through documentation of companies’ annual financial statements and analyzed using multiple linear regression with the assistance of IBM SPSS Statistics version 26. The results showed that, partially, company age, company size, and KAP size had no significant effect on audit delay, whereas auditor opinion had a significant effect on audit delay. Simultaneously, company age, company size, auditor opinion, and KAP size had a significant effect on audit delay. The conclusion of this study affirms that auditor opinion is an important factor that needs to be considered in the timeliness of audit completion, although company characteristics and KAP size do not always have a partial effect. These findings contribute to the development of agency theory and broaden understanding of the determinants of audit delay in energy industry and steel industry companies, while also providing practical implications for public companies in maintaining the credibility and timely submission of financial statements.